Antigone’s Claim: Hölderlin’s (and Hegel’s) Insights into a Legal and Genealogical Conundrum of the Tragedy - Kathrin Holzermayr L. Rosenfield (Humanities, 2025)
This approach to Hölderlin’s translation of Sophocles’ famous play modulates in significant ways the usual readings in which Antigone has become, over the centuries, an example of an early claim for natural law. Hölderlin’s insights inaugurate a new and innovative view that significantly affects this understanding. His version points to the authentically Greek legal aspect of Antigone’s position as an epicler daughter, claiming her dynastic prerogative to take over the palace and her father’s legacy. Hölderlin’s clues guide us to a reading that restores the tragic dilemma beyond the black-and-white Christian polarization of saintly Antigone and evil Creon and enhances both the heroine’s and Creon’s ambiguities in this rich and ironic text.